Fabrication of droplet based triboelectric nanogenerators (DB-TENGs) using lead free KNN-PVDF nanocomposite - Babita Sharma; Reema Gupta; Anjali Sharma; Arijit Chowdhuri; Monika Tomar (Chemical Physics Impact)
A highly efficient triboelectric energy harvesting system has been developed in the current work utilizing sheets of potassium sodium Niobate - polyvinyledene fluoride (KNN-PVDF) composite material. These composite sheets were prepared with different weight percentages of KNN (ranging from 10 % to 50 %) using the solution casting method to investigate the effect of KNN composition on structural and morphological properties. The XRD spectra confirms the orthorhombic phase of KNN in PVDF and well define linkages between KNN and PVDF is confirmed by the SEM images. The prepared sheets were further utilized for the application of Droplet based triboelectric nanogenerator (DB-TENG). It was found that the KNN-PVDF composite with 20 % KNN concentration exhibited an open circuit voltage of 1.56 V and short circuit current of 9.91 × 10 −6 A at a slope angle of 60° with NaCl concentration of 0.6 M in water, which corresponds to the molarity of ocean waves. The obtained results demonstrate the possible use of KNN-PVDF composite sheets for energy harvesting using sea waves.